2018
DOI: 10.1556/2006.7.2018.13
|View full text |Cite
|
Sign up to set email alerts
|

The links between healthy, problematic, and addicted Internet use regarding comorbidities and self-concept-related characteristics

Abstract: BackgroundAddicted Internet users present with higher rates of comorbidities, e.g., attention-deficit hyperactivity disorder (ADHD), depressive, and anxiety disorders. In addition, deficits in self-concept-related characteristics were found in addicted Internet gamers and social network users. The aim of this study was to examine the links between healthy, problematic, and addicted Internet use regarding comorbidities and self-concept-related characteristics. The association between recently developed ADHD-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 41 publications
5
40
0
Order By: Relevance
“…Previous works highlighted the relationship between PFU and Cluster B symptomatology such as borderline [35,40] and narcissism traits [41][42][43]. This is similar with results found with PIU for Cluster B [21,23,25,28] and Cluster C [21,25]. Borderline and antisocial traits have been frequently associated to addictive disorders, with impulsivity in common, which could be a supplementary evidence of the high similarity between PFU and other addictive disorders [44].…”
Section: Relationships With Pathological Personality Traitssupporting
confidence: 85%
See 1 more Smart Citation
“…Previous works highlighted the relationship between PFU and Cluster B symptomatology such as borderline [35,40] and narcissism traits [41][42][43]. This is similar with results found with PIU for Cluster B [21,23,25,28] and Cluster C [21,25]. Borderline and antisocial traits have been frequently associated to addictive disorders, with impulsivity in common, which could be a supplementary evidence of the high similarity between PFU and other addictive disorders [44].…”
Section: Relationships With Pathological Personality Traitssupporting
confidence: 85%
“…As for anxiety, mood disorders would have a causal relationship with PIU, as risk factors and consequences [20]. Besides, some studies highlighted the significant relationships between several pathological personality traits and PIU [21][22][23][24][25], yet no study focused on their relationships with SNS addictions, except for particular pathological traits. For example, borderline personality traits have been shown to be a risk factor for PFU [17], such as narcissistic personality traits, which also appeared to be related to Facebook and Twitter use [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Despite previous empirical evidence associating dysfunctional attachment and/or childhood trauma with problematic internet use and PSMU (Koronczai et al 2013;Lemenager et al 2018;Worsley et al 2018), the direct and indirect relationship of CEM and BID with PSMU and remains unexplored. Based on the aforementioned rationale, the present study examined the direct and indirect association of CEM with PSMU via BID using a sample of adolescents (see Fig.…”
mentioning
confidence: 96%
“…Individuals tend to cope with negative affect related to BID by using different maladaptive strategies (e.g., excessive eating, substance abuse) (Mitchison et al 2017;Nieri et al 2005). Past research has identified that some individuals engage in problematic internet use to avoid or relieve psychopathological symptoms (Lemenager et al 2018;Wegmann et al 2018), and/or to cope with low self-esteem associated with BID symptoms (Koronczai et al 2013). This is in line with the proposition that emotional problems (e.g., depression or anxiety symptoms) play a pivotal role in the emergence of problematic online behaviors (Kardefelt-Winther 2014; Wegmann and Brand 2016).…”
mentioning
confidence: 99%
“…Low conscientiousness is regarded as being disorganized, inefficient, careless and sloppy because these characteristics equate to a deficit in the executive functions. This could provide also provide an explanation for the comorbidity with ADHD (e.g., [70][71][72]). This theory is reinforced by previously reported findings.…”
Section: Discussionmentioning
confidence: 99%